MAN'S RELATIONSHIP WITH NATURE IN THE TAFSIR AL-IBRIZ AND AL-MISHBAH - Ali Abdur Rohman; Moh. Wafiq Faulal Ahsan (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This study aims to compare the interpretations of Al-Ibriz and Al-Mishab in relation to the relationship between humans and nature. The formulation of the problem raised by the author is: "How is the relationship between humans and nature in Al-Ibriz and Al-Mishbah and what is the difference between the two?" The analytical method used is muqaran. With the type of literature studied, the author makes Tafsir Al-Ibriz and Tafsir Al-Mishbah the primary sources and literature in the form of books and articles related to themes the secondary sources. The results of this study are, first, that the relationship between humans and nature appears in actions that lead to the destruction of nature, namely QS. Al-A'raf: 56. In Tafsir al-Ibriz, acts of destruction are defined as acts of shirk and immorality. Whereas in Tafsir Al-Misbah, vandalism is an act that exceeds the limit, both in terms of its physical, spiritual, and natural surroundings. Second, in QS. Yasin: 33-35 of Tafsir Al-Ibriz, it is stated that humans are ordered to maximize the role of reason in preserving nature as a form of gratitude to Allah SWT. Whereas in Tafsir Al-Mishbah, humans play a direct role in preserving nature, the essence remains Allah SWT, who determines.